VISÃO BASEADA EM RECURSOS: ANÁLISE COMPARATIVA ENTRE EMPRESAS FRANQUEADAS E NÃO FRANQUEADAS DO SETOR DE SERVIÇOS DE ALIMENTAÇÃO - Castilho, Sandro (2019)
Related to Resource Based View (RBV) Theory, it is known that the resources are linked to the organizations development, thus Nijmeijer, Huijsman and Fabbricotti (2014) assert that different projects must have distinct results, when professionals who use the franchise system as model, they must consider its business project to get better results. By these perspectives, it was researched the used resources, presuming that franchised enterprises and not franchised have different resources. The research wants to answer the question: Is there difference to use of resources between franchised enterprises and not franchised already established in Guarapuava town? Do these resources constitute main factor to enterprises development? The goal is to analyse if there is difference to use the resources between franchised and not franchised already established in Guarapuava town and if these resources may determine enterprises development. The research justifies through observed development in the eating segment and, also, in the franchising development, according to Brazilian Franchising Association (2018) the eating segment represents the biggest franchised invoicing. Related to methodological aspect this research has had quantitative approach, with descriptive character, field survey with primary data and ex-post-facto procedure. In order to structure the research, the resources were divided in four aspects, according to Barney and Hesterly (2007): Phisical Capital Resource, Human Capital Resource, Organizational Capital Resource and Financial Capital Resource. To collect the data, it was used printed questionnaires, which were delivery personally to investigated the population. Those resources were measured by Likert scale with 5 points, after that they were submitted to Kolmogorov and Smirnov tests in order to verify the data normality, statistics average tests, alpha Cronbach, correlation test of Spearman, Pearson correlation, test T and linear regression, to prove or refuse three hypotheses, the first is: Resources (physical capital, human capital, organizational capital, financial capital) are different between franchised enterprises and not franchised already established; the second: Development of franchised enterprises is different and better than the ones are not franchised; and the third: Resources (physical capital, human capital, organizational capital, financial capital) persuade the enterprises development. Results from the first hypotheses are proved by descriptive statistics tests and test T, thus the resources are different between franchised enterprises and not franchised. Therefore, the franchised enterprises conquer up average compared to not franchised enterprises in all constructs. However, the hypothesis number 2, which had its validity tested by descriptive statistics and T test, the results show that this hypothesis is not confirm, because the statistics data show similar average between the two groups, franchised and not franchised. The third and last hypothesis, which had its approval tested by linear regression, this was partial confirmed, because only the human capital have meaningful influence on development, this construct explains more than 30% of its development, and the others were explained by variables not deliberate at this research. Others resources do not have direct relation, although was observed that even it does not have a direct influence on development, the physical capital resources and financial capital resources have major persuasion on invoicing variation.